Photoluminescent properties of ZrO2: Tm3+, Tb3+, Eu3+powders—A combined experimental and theoretical study - Lovisa, L. X.; Andrï¿½s, J.; Gracia, L.; Li, M. S.; Paskocimas, C. A.; Bomio, M. R.D.; Araujo, V. D.; Longo, E. [UNESP]; Motta, F. V. (Elsevier, 2017)
Rare-earth (RE) element-based materials for optical applications have received increasing attention owing to the emission properties of RE ions, which render these materials suitable for use in color displays, lasers, and solid-state lighting. In the present work, ZrO2:RE (RE = Tm3+, Tb3+, and Eu3+) powders were obtained via complex polymerization, and characterized by means of X-ray diffraction (XRD), Raman spectroscopy, UV–visible absorption spectroscopy, and photoluminescence measurements. The XRD patterns and Raman spectra revealed the tetragonal phase of ZrO2co-doped with up to 4 mol.% RE3+and stabilization of the cubic phase, for up to 8 mol.% RE3+. In addition, the photoluminescence measurements revealed simultaneous emissions in the blue (477 nm), green (496.02 nm and 548.32 nm), and red-orange (597.16 nm and 617.54 nm) regions. These emissions result from the Tm3+, Tb3+, and Eu3+ions, respectively. Energy transfers, such as1G4levels (Tm3+) →5D4(Tb3+) and5D4levels (Tb3+) →5D0(Eu3+), occurred during the emission process. Calculations based on density functional theory (DFT) were performed, to complement the experimental data. The results revealed that structural order/disorder effects were generated in the cubic and tetragonal ZrO2phases in the ZrO2:Eu3+powders, and changes in the electronic structure were manifested as a decrease in the band gap values. The chromaticity coordinates of all the samples were determined from the PL spectrum. The coordinates, x = 0.34 and y = 0.34, of the ZrO2:8%RE sample corresponded to a point located in the white region of the CIE diagram and color correlated temperature (CCT) was found to be 5181 K. More importantly, the present results indicate that ZrO2:RE powders constitute promising photoluminescent materials for use in new lighting devices.
Keywords: DFT calculations; Photoluminescence; White LEDs; ZrO2:RE